The Use Of E-Commerce As A Marketing Strategy To Sustain Muslim And Muslimah Clothing Stores - Harmiyanti, Yuni; Sarmigi, Elex; Bustami, Yuserizal (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study examines how e-commerce serves as a marketing strategy to support Muslim and Muslimah clothing stores in Sungai Penuh City. In today's digital age, e-commerce is a vital tool for enhancing business competitiveness through platforms like marketplaces, social media, and Google Business. Using a qualitative descriptive method, data were gathered via interviews, observations, literature review, and documentation. The results indicate that many stores have adopted digital marketing through Shopee, Tokopedia, Facebook, and Instagram. E-commerce has enabled stores to reach wider markets, attract more customers, and improve brand recognition. Challenges such as price competition, low digital literacy, and logistical issues persist. However, with suitable digital marketing strategies, these stores can remain competitive and grow. Creating engaging content and fostering active customer participation on digital platforms are crucial for maintaining business sustainability in the e-commerce landscape.